How emotion is experienced and expressed in multiple cultures: a large-scale experiment across North America, Europe, and Japan - Cowen, Alan S.; Brooks, Jeffrey A.; Prasad, Gautam; Tanaka, Misato; Kamitani, Yukiyasu; Kirilyuk, Vladimir; Somandepalli, Krishna; Jou, Brendan; Schroff, Florian; Adam, Hartwig; Sauter, Disa; Fang, Xia; et al. (Frontiers in Psychology, 2024)
Core to understanding emotion are subjective experiences and their expression in facial behavior. Past studies have largely focused on six emotions and prototypical facial poses, reflecting limitations in scale and narrow assumptions about the variety of emotions and their patterns of expression. We examine 45,231 facial reactions to 2,185 evocative videos, largely in North America, Europe, and Japan, collecting participants’ self-reported experiences in English or Japanese and manual and automated annotations of facial movement. Guided by Semantic Space Theory, we uncover 21 dimensions of emotion in the self-reported experiences of participants in Japan, the United States, and Western Europe, and considerable cross-cultural similarities in experience. Facial expressions predict at least 12 dimensions of experience, despite massive individual differences in experience. We find considerable cross-cultural convergence in the facial actions involved in the expression of emotion, and culture-specific display tendencies—many facial movements differ in intensity in Japan compared to the U.S./Canada and Europe but represent similar experiences. These results quantitatively detail that people in dramatically different cultures experience and express emotion in a high-dimensional, categorical, and similar but complex fashion.